Threatening Stances : a corpus analysis of realized vs. non-realized threats - Gales, Tammy (Language and Law / Linguagem e Direito, 2017)
Stance provides a link between individual performance and meaning (Jaffe, 2009); affective and epistemic markers of stance, in particular, serve to demonstrate the stance-taker’s perceived level of emotion towards and commitment to the mentioned proposition. As such, these markers are oftentimes used by law enforcement practitioners to help determine a threatener’s commitment to carrying out their threatened action. Yet, previous research has revealed that stance markers do not always function in expected ways (e.g., Conrad and Biber, 2000). Thus, through a corpus analysis of 104 authentic threats, this paper examines the distribution and function of grammatical stance markers within threats that were carried out vs. those that were not. Specifically, it is argued that the social sanction (Martin and White, 2005) against carrying out threats, i.e., arrest, prosecution, and jail time, may socially affect the ways in which writers use grammatical markers of stance that demonstrate their level of perceived emotion and commitment, thus blurring the lines between threats that are realized and those that are not realized. The results demonstrate how ideologies about threatening language frequently conflict with authentic language practices and create “a totalizing vision” of threatening language, rendering any linguistic features and functions not consistent with the ideologies invisible (Irvine and Gal, 2000: 38).